Atividade antioxidante e antibacteriana e compostos fenólicos totais de extratos de fungos filamentosos produtores de pigmento - Tavares, Dérica Gonçalves (2017)
The objectives of this work were to evaluate the activity of the ethyl acetate extracts of pigment-producing filamentous fungi in the inhibition of pathogenic bacteria transmitted by food, determining their minimum bactericidal concentration (MBC). The evaluation of the antioxidant activity using the DPPH and the ABTS •+ free radical sequestration methods, the β-carotene-linoleic acid system and the content of total phenolic compounds by the Folin Ciocalteu method were also carried out. Twelve isolates of filamentous fungi selected by their pigment production in solid culture medium were identified using the sequences of the internal transcribed spacer (ITS) 5.8S region of rDNA and RNA polymerase II second largest subunit (RPB2). The following species were identified: Aspergillus keveii (CML 2968), Aspergillus sydowii (CML 2967), Penicillium chermesinum (CML 2966), Epicoccum nigrum (CML 2971, A2C32 and A2S61), Periconia ignaria A2C47) and Lecanicillium aphanocladii ( CML 2970). Furthermore, the genera Arcopilus sp. (A2C54) and F. graminearum sensu lato (CML 2969) were identified. Five isolates showed bactericidal activity against at least one pathogenic bacteria strain. The extracts of A. sydowii (CML 2967) and A. keveii (CML 2968) showed MBC of 5 mg mL -1 , while for Fusarium sp. (CML 2969) the MBC ranged from 5 to 0.625 mg mL -1 and for P. ignaria (A2C47) the MBC ranged from 5 to 1.25 mg mL -1 . The extract of the endophytic fungus Arcopilus sp. (A2C54) exhibited the highest bactericidal activity, with MBC 0.00244 and 0.0195 mg mL -1 against Staphylococcus aureus GL 8702 and GL 5674, respectively, and 0.625 mg mL -1 for Salmonella Enteritidis. The extract of P. flavigenum (CML 2965) showed the highest antioxidant activity in all the used methods with 98.22 % inhibition of the DPPH and EC50 of 83.4 μg mL -1 ; 29.50 % inhibition of ABTS •+ and EC50 of 862.2 μg mL -1 ; and 72.23% protection of β-carotene. The total concentration of phenolic compounds was 201.43 mg GAE g -1 extract. The results show the potential of these filamentous fungi as new sources of antibacterial and antioxidant metabolites that may have biotechnological applications in the future.